‘Patients’ experiences of Enhanced Recovery after Surgery’ - Bernard, Helena (2012)
Aim To investigate ‘patients’ experiences of enhanced recovery after surgery (ERAS).’ Background ERAS is a multi-modal pathway whose strong evidence-base is changing the methods used to care for patients before, during and after elective surgery. As a result, patients are being safely discharged at a much earlier stage than has previously been thought possible. Literature concentrates on the surgical and economical benefits of ERAS, leaving little doubt that the programme holds much potential for the future of surgical care. But, there is a lack of research evidence into the patients’ perspective of the programme. Therefore, this study investigates patients’ experience of ERAS to determine the issues of importance to them. Methodology Semi-structured interviews were conducted to collect data on the experiences of ERAS patients. Interviews were tape-recorded and transcribed and the qualitative technique of thematic analysis, based on a grounded theory approach, was used to analyse the data. Findings and discussion The issues of significance to participants were grouped under 4 themes: information provision, in-patient experiences, home recovery experiences and psychological and emotional experiences. Although participants reported many good aspects of their vii ERAS experience, the findings highlighted the need for improvement in 4 key areas: better information provision, more appropriate discharge planning, improved post-discharge support from both from community services and hospital follow-up and more emphasis on addressing the psychological needs of ERAS patients. Conclusion and recommendations The study concluded that patients are positive about ERAS but that aspects of the programme are negatively impacting on their experience, particularly relating to a lack of psychological support and an absence of high quality community care post-discharge. The recommendations to enhance patients’ experiences of ERAS are to: create standardised patient and carer information packs, provide all patients with an outpatients consultation post-discharge, educate the MDT on the care of ERAS patients, ensure that patients have adequate home support prior to discharging them, establish a clearer process for accessing support and advice post-discharge and develop an intervention to help patients cope with the psychological pressures of ERAS.